ADDRESSING CHALLENGES IN ENGLISH SPEAKING SKILLS IN COLLEGE THROUGH DRAMA PERFORMER: A CASE STUDY - Muhammad As'ad (International Journal of Social Science, 2025)
English speaking skills are crucial for academic and professional success, yet college students face internal (e.g., lack of confidence, fear of judgment) and external challenges (e.g., limited practice opportunities). This study explored the use of educational drama to enhance these skills through Classroom Action Research (CAR) conducted in two cycles. Activities included role-playing, improvisation, and real-life simulations. Results showed marked improvements in speaking accuracy (Cycle I: +47.49%, Cycle II: +13.17%) and fluency (Cycle I: +18.51%, Cycle II: +14.30%). Student engagement rose from 70.6% to 99.6%. Despite challenges like low participation and classroom management, adjustments in Cycle II proved effective. The study highlights educational drama as a transformative approach to building confidence, vocabulary, and fluency, recommending future research on motivation and classroom optimization